Long Non-coding RNA H19 Augments Hypoxia/Reoxygenation-Induced Renal Tubular Epithelial Cell Apoptosis and Injury by the miR-130a/BCL2L11 Pathway - Yuan, Yuan; Li, Xiaoling; Chu, Yudong; Ye, Gongjie; Yang, Lei; Dong, Zhouzhou (Frontiers in Physiology, 2021)
Acute kidney injury (AKI) is a severe disease defined by partial or total loss of kidney function. Accumulating evidence has reported that non-coding RNAs, particularly long non-coding RNAs (lncRNAs), participated in regulating AKI development. Here we aimed to explore how LncRNA H19 and miR-130a are regulated in renal tubular epithelial apoptosis. The expressions of LncRNA H19, miR-130a and inflammatory cytokines were measured by RT-qPCR and ELISA assays. Kidney tubular cells HK-2 were injured with CoCl2 to induce cell damage model. After treatment, the effects of LncRNA H19 and miR-130a on HK-2 cell proliferation and apoptosis under H/R treatment were investigated. Finally, the reciprocal inhibition among LncRNA H19, miR-130a and BCL2L11 was elucidated. Down-regulation of LncRNA H19 could regulate inflammatory cytokines expressions, promote cell proliferation and inhibit apoptosis in HK-2 cells treated with H/R through targeting miR-130a. However, the variation caused by LncRNA H19 could be revered by BCL2L11which is targeted by miR-130a. In a word, high level of LncRNA H19 may enhance HK-2 cells injury induced by hypoxia through miR-130a/BCL2L11 pathway. Therefore, LncRNA H19 could be a promising diagnostic markers and therapeutic target for early stages of AKI.